Developing a Simple Scanning Probe System for Soft X-ray Spectroscopy with a Nano-focusing Mirror - Ando, Hiroshi; Horio, Masafumi; Takeo, Yoko; Niibe, Masahito; Wada, Tetsuya; Ando, Yasunobu; Kondo, Takahiro; Kimura, Takashi; Matsuda, Iwao (E-journal of surface science and nanotechnology, 2023)
We developed a compact system for the spectroscopic mapping of a microstructure with a nano-focused beam at a soft X-ray beamline of synchrotron radiation. The experimental setup comprises a Wolter mirror and sample that are arranged with two mounting stages. The Wolter mirror is aligned with three degrees of freedom, and the sample with two degrees. The system generates a beam with an 800-nm spot and maps out a chemical distribution of non-uniform material through near-edge X-ray fine structure spectroscopy. The design and actual system are suited to experiments conducted with a nano-focused X-ray beam at beamlines of synchrotron radiation or an X-ray free-electron laser. Additionally, this technical note presents guidelines for actual experiments.